TEACHERS’ DIFFICULTIES IN ONLINE ASSESSMENT FOR STUDENTS IN TEACHING ENGLISH DURING PANDEMICS - Musdalifah; Ummi Khaerati Syam; Andi Asri Jumiaty (Journal of Language Testing and Assessment, 2022)
Since the COVID-19 pandemic last year, the government announced that learning would be moved online. This results in teacher assessments of students having to be done online. This research was conducted to find out how online assessment is applied by teachers in schools, especially in learning English. This study aims to determine whether teachers have difficulties and what difficulties are encountered by teachers in conducting online assessments, as well as how teachers overcome their difficulties. This study uses qualitative research methods and the subject of this research is an English teacher in SMPN 4 Bantimurung Kab. Maros. This study uses interviews and questionnaires as research instruments, interview questions and questionnaires to find out the difficulties of teachers in conducting online assessments and the implementation during the covid-19 pandemic.